2006
DOI: 10.1007/s11199-006-8869-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Simple Visual Reaction Time: A Historical Meta-Analysis

Abstract: To test the hypothesis that the magnitude of sex differences in simple visual reaction time (RT) has narrowed across time, a meta-analysis was conducted on 72 effect sizes derived from 21 studies (n = 15, 003) published over a 73-year period. The analysis provided strong evidence for the hypothesized change. In addition, the analysis indicated that the sex difference in RT was on average smaller with non-U.S. samples than with U.S. samples. No relation was found between the magnitude of the sex difference in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 47 publications
8
66
5
2
Order By: Relevance
“…In line with prior studies (Camarata & Woodcock, 2006;Feingold, 1992;Longman et al, 2007;Majeres, 2007;Reynolds et al, 1987;Sheppard & Vernon, 2008;Silverman, 2006;Wechsler, 1997), our findings indicated that gifted girls were significantly better than gifted boys in processing speed which was measured through WISC-R Coding subtest. Although the findings of this study together with those of previous research might confirm female superiority in processing speed, we have no theoretical explanations for these differences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with prior studies (Camarata & Woodcock, 2006;Feingold, 1992;Longman et al, 2007;Majeres, 2007;Reynolds et al, 1987;Sheppard & Vernon, 2008;Silverman, 2006;Wechsler, 1997), our findings indicated that gifted girls were significantly better than gifted boys in processing speed which was measured through WISC-R Coding subtest. Although the findings of this study together with those of previous research might confirm female superiority in processing speed, we have no theoretical explanations for these differences.…”
Section: Discussionsupporting
confidence: 90%
“…Although findings vary based on the type of tasks used, women are found to be faster on tests of processing speed including the digit and symbol coding task of the Wechsler tests (Camarata & Woodcock, 2006;Feingold, 1992;Longman, Saklofske, & Fung, 2007;Majeres, 2007;Reynolds, Chastain, Kaufman, & MacLean, 1987;Sheppard & Vernon, 2008;Silverman, 2006;Wechsler, 1997). For example, Longman et al (2007) studied gender differences on Wechsler Adult Intelligence Scale -III index scores in the American (n= 2450) and Canadian (n= 1104) standardization samples.…”
Section: Gender Differences In Processing Speed and Creativitymentioning
confidence: 99%
“…Gender and age were not significant, which is in contrast with previous research on absolute RT that found faster movement time for male and young drivers (e.g., Schweitzer et al, 1995;Welford, 1977), but corroborate more recent hypotheses that it is the covariate of actual driving experience that impacts more on overall BRT in real-life driving, rather than the absolute value of being young/old, male/female drivers (Olson and Sivak, 1986;Silverman, 2006). Moreover, the visibility and driving condition used in this test were not critical, and so the eventual differences that can be generated by different exposure to driving usually related to gender and age, were probably not highlighted in this type of tests.…”
Section: Discussionsupporting
confidence: 75%
“…However, this reliability is similar or better as compared with reliability of other computerized RT tests involved in the neuropsychological test batteries as the ImPact with 1 week testretest reliability ICC = .78-.88 in young adults subjects (Resch et al, 2013), the ANAM battery with 1 week test-rest reliability r = .29-.46, and ICC = .24-.38 in the adolescents (Segalowitz et al, 2007), and the Cogsport tests with 2 weeks test-retest reliability ICC = .73 for SRTs, and ICC = .65 for CRTs in football players (Straume-Naesheim, Andersen & Bahr, 2005). The logical limitation of the study is that interpretation of the findings are valid for male adolescents only due to age and sex differences in RTs and their intra-individual variability (Dykiert et al, 2012a(Dykiert et al, , 2012Silverman, 2006).…”
Section: Discussionmentioning
confidence: 98%